Chemical composition of petroleum from Krapivinskoye oilfield (message 3) - Valeriy Petrovich Sergyn; Tatyana Viktorovna Cheshkova; Tatyana Anatolievna Sagachenko; Raisa Sergeevna Min (Известия Томского политехнического университета: Инжиниринг георесурсов, 2017)
Relevance of the research is caused by the need in information on the composition and structure of the asphaltene components in the Upper Jurassic methanonaphthenic oil from the Krapivinsk oilfield located in Tomsk region to solve the problems related to oil production, transportation and processing. The aim of the work is to characterize the composition of asphaltenes in the Krapivinsk oil and structural fragments bound in their molecules through sulfide and ether bridges. Research methods: extraction, liquid-adsorption chromatography, selective chemical destruction of sulfide and ether bonds, IR spectroscopy, chromatography-mass spectrometry. Results. It was ascertained that asphaltenes of methanonaphthene oil contain high- and low-molecular components and compounds adsorbed or occluded by their molecules («maltenes»). The structure of asphaltenes includes the fragments connected with each other or with a nucleus of asphaltene molecules by ether and sulfide groups. Normal and branched alkanes, alkenes with even number of carbon atoms in the chain, mono< and polycycloalkanes, mono-, bi-, tri-, tetra- and pentacyclic aromatic hydrocarbons, dibenzothiophenes and fatty acids are the main representatives of such fragments. Among the compounds, adsorbed/occluded by the macromolecules of the asphaltene components under study, normal and branched alkanes, alkenes with an even number of carbon atoms in the chain, alkylcyclopentanes and alkylcyclohexanes, steranes and terpanes, mono-, bi- and trisubstituted alkylbenzenes, naphthalenes, phenanthrenes, benzo- and dibenzothiophenes, dibenzofurans, benzo- and dibenzocarbazoles were identified. The presence of the identified compounds in «maltenes» can be caused by both their sorption on macromolecular formations of asphaltenes and clathration with nanoaggregates particles of asphaltenes that have captured these compounds in the hollow cells of their structures at the early stages of oil systems formation.